IMPLEMENTASI PROGRAM PENDIDIKAN FORMAL UNTUK ANAK PENGUNGSI OLEH DINAS PENDIDIKAN DI KOTA PEKANBARU - Wika Wahyuni; Irdayanti Irdayanti (Sultan Syarif Kasim State Islamic University, Riau, 2023)
The purpose of this study is to describe the implementation of formal education programs for refugee children by the Education Office in Pekanbaru City. On the basis of the policy of the Circular of the Ministry of Education of the Republic of Indonesia Number. 75253/A.A.4/HK/2019. This study uses qualitative research with descriptive methods. Data collection techniques with observation, interviews and documentation. To explain program implementation according to Daniel A. Mazmanian and Paul A. Sabatier, there are three indicators, namely the (Tractability of the problems), (Ability of statute to structure implementation), and (Nonstatutory variables affecting implementation). The results of this study can be concluded that the implementation of a formal education program for refugee children by the Education Office in Pekanbaru City has been implemented, but from a comparison with the number of refugee children currently attending formal school with the number of children who have entered school age there are still many children refugees who have not attended school. Especially at the junior high school level, very few refugee children attend school. The researcher also found several findings, namely the data obtained from the Education Office did not match the reality that occurred in the field, that in one school there were no longer refugee children who attended school there and also in several schools the number of children attending school was no longer appropriate. the number is recorded at the Education Office but the data is not updated by the Education Office, this is due to a lack of oversight from the Education Office